Dumpster diving jako pramen kreativity - Brunclíková, Lenka; Kliková, Jana (Lidé města, 2018)
This paper aims to present dumpster diving as a source of creativity. We argue that thanks to dumpster diving, the pickers exhibit some forms of creative behaviour that would otherwise be concealed or suppressed. We understand creativity as “creativity forward” (Ingold and Hallam 2007), which means considering the process of being creative itself rather than any tangible innovative result that might come from this process. Our view differs from the concepts of creativity and innovation in the fields of business or technology, where the particular, and more importantly, useful result of the creative process is taken as the criterion for creativity. Since dumpster divers face multiple obstacles during their activities, they are forced to creatively come up with solutions and to flexibly respond to whatever issues emerge. In contrast to customary shopping, dumpster divers are also challenged by the issue of how to consume an excessive amount of one type of food so as to not dispose of it again.